Media Literacy of Science Teachers and Application Approach for Students Development in Primary Education Level Chonburi Province - Aiemsakul, Sojirat; Sirisawat, Chade; Kosaiyawat, Suwichai; Thamwattana, Maytee (Academic Journal of Mahamakut Buddhist University Roi Et Campus, 2020)
The objective of this research article were 1) to study science media literacy of primary education science teachers in Chonburi Province, 2) to study the approach to enhance the science media literacy of the science teachers. 3) to study guidelines for the development of science literacy for science teachers.The quantitative data were collected survey questionnaire with 67 primary school science teachers. The statistical methods for analyzing the data were percentage, mean, and standard deviation. The qualitative data were collected from the interview of 10 head teachers of science department and 3 science teachers by using Purposive Sampling, the data were analyzed by descriptive content analysis. The results of the research revealed that : 1. Science teachers had science media literacy of concerning accessing at the high level, followed by analyzed at the high level. Evaluation techniques was found at the high level, Participation was at the high level respectively. The science teachers had created media for science literacy (70.8%). Science teachers did not created media for science literacy (29.2%). 2. The way to enhancing the science media literacy of science for students are activities workshop training course in a topic of science media literacy, establishing science media literacy club activities and 3. the way to enhancing the science media literacy of science teachers are outdoor activity to discover new things, creating new science media that has not been done before to stimulate students’ attention.